An Investigation of Facets and Microsenses of Words in Persian - S. Hamzeh Mousavi; Seyed Mohammad Mousavi (نشریه پژوهش‌های زبان‌شناسی)
This paper aims to explore the facets and microsenses of Persian words and examine the impact of cultural and social factors on the emergence of novel meanings. To deeply study these phenomena, a series of words exhibiting facets or microsenses was selected from a diverse range of texts. Subsequently, the Persian Academy Corpus was employed to identify additional examples of each word, thereby facilitating a comprehensive exploration of facets and microsenses associated with each lexical item. A descriptive-analytic methodology was then applied to Analyse the collected data. The findings reveal that the activation of facets within a word is context-dependent, with varying degrees of activation possible. Additionally, the paper demonstrates that facets and their surrounding lexical items mutually influence each other. Finally, the study suggests that novel facets and microsenses, distinct from homonymy and polysemy, can arise as a result of cultural and social influences.